Robust scalar-on-function partial quantile regression - BEYAZTAŞ, UFUK (My University, 2023)
Compared with the conditional mean regression-based scalar-onfunction regression model, the scalar-on-function quantile regression is robust to outliers in the response variable. However, it is susceptible to outliers in the functional predictor (called leverage points). This is because the influence function of the regression quantiles is bounded in the response variable but unbounded in the predictor space. The leverage points may alter the eigenstructure of the predictor matrix, leading to poor estimation and prediction results. This study proposes a robust procedure to estimate the model parameters in the scalar-on-function quantile regression method and produce reliable predictions in the presence of both outliers and leverage points. The proposed method is based on a functional partial quantile regression procedure. We propose a weighted partial quantile covariance to obtain functional partial quantile components of the scalar-on-function quantile regression model. After the decomposition, the model parameters are estimated via a weighted loss function, where the robustness is obtained by iteratively reweighting the partial quantile components. The estimation and prediction performance of the proposed method is evaluated by a series of Monte-Carlo experiments and an empirical data example. The results are compared favorably with several existing methods. The method is implemented in an R package robfpqr.
Keywords: İstatistik; Temel Bilimler; Statistics; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; Psikoloji; ÇOK DİSİPLİNLİ BİLİMLER; PSİKOLOJİ, MATEMATİKSEL; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; PSYCHOLOGY; MULTIDISCIPLINARY SCIENCES; PSYCHOLOGY, MATHEMATICAL; Multidisipliner; Multidisciplinary